Development of a student-centred approach for alternative teaching method incorporating human palpation as pedagogy tools in anatomy education of the appendicular system - Gan, QF; Yu, CW; Alkharji H; Foo, CN (Penerbit Universiti Kebangsaan Malaysia, 2024)
Anatomy is one of the most important subjects for medical and health science students offered during pre-clinical years. A good knowledge in human anatomy determines their competency in the future. Unfortunately, memorising anatomy can be relatively challenging especially for junior students since they are not exposed to the nomenclature. Therefore, this study aimed to design and develop an anatomy curriculum to assist students in knowledge retention and translation into clinical settings. The development of this module was based on social cognitive theory (SCT) according to A-Analysis, D-Design, D-Develop approach which was adopted from A-Analysis, D-Design, D-Develop, I-Implement, E-Evaluate (ADDIE) Model, together with the content experts. Due to the concern of comprehending and practically applying anatomical knowledge, and short attention spans of students, the module was designed to alternate between lectures and practical sessions to maximise knowledge retention. The main focus on this curriculum module was on the gross anatomy of the appendicular system and ends with students being required to palpate and compare the differences between normal and pathological structures of the appendicular system. This curriculum effectively addressed the issue of short attention spans by incorporating hands-on experiences, and engaging students in tactile learning that enhanced focus and engagement.